Is there any association between childhood trauma and chronic dermatological diseases? A case-control study - Kaya İslamoğlu, Zeynep Gizem; Ulutaş Demirbaş, Gözde; Unal, Mehmet; Aydın, Memduha (Journal of Surgery and Medicine, 2019)
Aim: It is known that traumatic experiences in childhood cause many psychosomatic and psychodermatological diseases. Common dermatological diseases bring abaout not only dermatological but also psychosocial problems. In our study, we aimed to investigate association of depression, anxiety and childhood trauma with chronic dermatological diseases. Methods: After power analysis, 76 patients with chronic dermatological diseases (study group) and 75 healthy volunteers (control group) were included in this study. Beck Anxiety Inventory, Beck Depression Inventory and Childhood Trauma Scale (CTQ 28) were administered to these individuals. Results: The anxiety (p=0.001) and depression (p<0.001) levels were higher in the study group than control group. However, there was no difference with CTQ 28 total (p=0.217) and subscales scores (p=0.159, p=0.976, p=0.902, p=0.234 and p=0.267, respectively) between groups. Physical neglect scores differed significantly according to educational status in the patient group (F=3.643, p=0.031). Emotional neglect and total CTQ 28 scores were higher in patients with lichen simplex chronicus (p=0.234). Conclusion: In our study, unlike previous studies, dermatological diseases such as lichen planus, Behçet’s disease, choronic urticaria, vitiligo were included in the study. These group of diseases should be considered because they adversely affect every aspect of patients' lives in almost. Patients should be carefully evaluated for psychiatric support. We think that the detailed investigation of traumatic experiences from both dermatologists and psychiatrists can lead to better results in the treatment of chronic patients by using psychotherapeutic interventions.